Uji Efek Analgesik Ekstrak Buah Andaliman (Zanthoxylum Acanthopodium) Terhadap Nyeri Pada Mencit (Mus Musculus) Yang Diinduksi Asam Asetat - Mei Riauly Wira; Petri Lumban Gaol; Boyke Marthin Simbolon (Jurnal Infokes, 2021)
Pain is an unpleasant sensory and emotional experience which is the result of stimulus by damaged tissue or chemical mediators which can be experienced by range of intensity, quality, duration, distribution and location. Pain can be resolved pharmacologically by non-opioid (NSAID, salicylates) or opioid (morphine) drugs. Alternatively, pain also can be resolved by non-pharmacological intervention such as hot/cold compress, TENS, behavior therapy, or relaxation therapy. Andaliman (Zanthoxylum acanthopodium), generally used as spices in North Sumatera, also can be utilized as pain killer (analgesic). Objective: To determine the effectivity of Andaliman fruit extract (Zanthoxylum acanthopodium) as analgesic in mice (Mus muscular). Methods: This research is an experimental study with posttest only control group design. Experiment conducted to the mice by using 1% acetate acid to induce pain and then intervened by using mefenamic acid or Andaliman fruit extract in different doses and followed by observation of the pain response for 60 minutes with 5 minutes intervals between observation. Result: Andaliman fruit extract in the dose of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW have analgetic effectivity more than 50% compared to mefenamic acid with effectivity of 93,16%, 89,21%, and 112,01% respectively. Conclusion: Andaliman fruit extract is an effective analgesic.